The effect of financial hedging on the incentives for corporate diversification: The role of stakeholder firm-specific investments - LIM, Sonya Seongyeon (Institutional Knowledge at Singapore Management University, 2007)
Financial hedging and corporate diversification are often considered substitutive means of risk management, implying that rapid development of financial hedging markets will yield less need for firms to manage risk through costly diversification. Building on a stakeholder-based view of risk management, we show that financial hedging and corporate diversification are more often complementary than substitutive. Financial hedging reduces a firm’s systematic risk, encouraging firm-specific investment by stakeholders. Larger firmspecific investment loads excessive idiosyncratic risk on the stakeholders, increasing the benefits of reducing idiosyncratic risk through diversification. Therefore, financial hedging can increase a firm’s incentives to manage risk through diversification.